Efficacy of Intra-Arterial Plus Intravesical Chemotherapy for High-Risk Non-Muscle-Invasive Bladder Cancer: A Pooled Analysis - Chunliang Cheng; Dongxu Qiu; Jinbo Chen; Xiongbing Zu; Jinhui Liu; Huihuang Li; Jiao Hu; Zhenglin Yi; Tongchen He; Zhi Chen; Yu Cui (Frontiers Media S.A., 2021)
Background: The treatment for high-risk non-muscle-invasive bladder cancer (NMIBC) remains highly debated for its high recurrence and progression risk. This work aimed to verify the efficacy and toxicity of intra-arterial chemotherapy (IAC) plus intravesical chemotherapy (IVC) in high-risk NMIBC.Methods: A comprehensive online literature search was conducted in three databases to select researches related to IAC + IVC for high-risk NMIBC. All data were analyzed using the Review Manager software version 5.3. And we used the Cochrane Risk of Bias tool to assessed the quality of these enrolled researches.Results: Seven eligible original publications were enrolled in our studies with a total of 1,247 patients. Compared with the intravesical instillation, IAC + IVC therapy showed a better therapeutic effect. The total odds ratio for tumor recurrence rate, tumor progression rate, survival rate, and tumor-specific death rate was calculated as 0.51 (95% CI: 0.36-0.72; p < 0.05), 0.51 (95% CI: 0.36-0.72; p < 0.05), 1.75 (95% CI: 1.09-2.81; p < 0.05), and 0.48 (95% CI: 0.28-0.84; p < 0.05), respectively. In patients who received IAC, most of the adverse events (AEs)in the treatment were Grade I and II.Conclusion: IAC + IVC regimen for high-risk NMIBC could effectively reduce recurrence and progression and provide a better prognosis than intravesical instillation. The adverse events of IAC were mild and acceptable.